A keystone ant species promotes seed dispersal in a "diffuse" mutualism - Majer, Jonathan; Gove, Aaron; Dunn, Robert (2007)
In order to understand the dynamics of co-evolution it is important to consider spatial variation in interaction dynamics. We examined the relative importance of ant activity, diversity and species identity in an ant seed dispersal mutualism at local, regional and continental scales. We also studied the determinants of seed dispersal rates and dispersal distances at eight sites in the Eneabba sandplain (29.63 S, 115.22 E), western Australia to understand local variation in seed dispersal rate and distance. To test the generality of the conclusions derived from the eight local sites, we established 16 sites along a 1650-km transect in western Australia, covering 11° of latitude and a six-fold increase in rainfall, at which we sampled the ant assemblage, estimated ant species richness and ant activity and observed the removal rate of myrmecochorous seeds. We also assessed the importance of ant species identity at a continental scale via a review of studies carried out throughout Australia which examined ant seed dispersal.